2014
DOI: 10.1177/1932296814532906
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Calculators

Abstract: Matching meal insulin to carbohydrate intake, blood glucose, and activity level is recommended in type 1 diabetes management. Calculating an appropriate insulin bolus size several times per day is, however, challenging and resource demanding. Accordingly, there is a need for bolus calculators to support patients in insulin treatment decisions. Currently, bolus calculators are available integrated in insulin pumps, as stand-alone devices and in the form of software applications that can be downloaded to, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 36 publications
2
112
0
1
Order By: Relevance
“…Insulin pumps have long offered bolus calculators which handle the I:C and correction factor calculations and account for active insulin on board (IOB), generally resulting in a positive impact on glycemic control . Similar bolus calculators are now available on some commercial blood glucose meters or as cell phone apps . The Automated Bolus Advisor Control and Usability Study (ABACUS) showed that significantly more patients using the bolus calculator achieved an HbA1c reduction of >0.5% compared to the control group (56% vs 34%; P < 0.01) .…”
Section: Diabetes Apps Automated Decision Support and Bolus Calculamentioning
confidence: 99%
“…Insulin pumps have long offered bolus calculators which handle the I:C and correction factor calculations and account for active insulin on board (IOB), generally resulting in a positive impact on glycemic control . Similar bolus calculators are now available on some commercial blood glucose meters or as cell phone apps . The Automated Bolus Advisor Control and Usability Study (ABACUS) showed that significantly more patients using the bolus calculator achieved an HbA1c reduction of >0.5% compared to the control group (56% vs 34%; P < 0.01) .…”
Section: Diabetes Apps Automated Decision Support and Bolus Calculamentioning
confidence: 99%
“…Alternatively, it can be achieved by a more flexible therapy approach in which people independently adapt insulin dosing, primarily mealtime insulin, to all other activities on a day-to-day basis. To meet the need for support in insulin bolus calculations a variety of bolus calculators have been developed [9]. This systematic method for insulin bolus calculation combines estimation of food carbohydrate content, blood glucose measurement, and evaluation of factors that may affect insulin sensitivity such as exercise, acute illness or stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several flexible insulin therapy strategies exist, one of which includes advanced carbohydrate counting [4,5]. Such advanced bolus calculators have been available to insulin pump users as integrated components of their pumps for several years, but automated bolus calculators targeting people treated with multiple daily injections have only recently been launched [9]. To estimate the amount of carbohydrate in a meal, knowledge about the carbohydrate content of different food products is required.…”
Section: Introductionmentioning
confidence: 99%
“…A first simple tool devised to provide decision support to T1D patients is the so-called bolus calculator [61], a software that implements a simple formula for computing the amount of insulin to inject subcutaneously which is expected to compensate for carbohydrates intakes. The formula for calculating the recommended dose of insulin, B (U) is:…”
Section: Bolus Calculatormentioning
confidence: 99%